2023
DOI: 10.3390/ijms24087342
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis-Related Molecular Clusters and Diagnostic Model in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by synovitis, joint damage and deformity. A newly described type of cell death, ferroptosis, has an important role in the pathogenesis of RA. However, the heterogeneity of ferroptosis and its association with the immune microenvironment in RA remain unknown. Synovial tissue samples from 154 RA patients and 32 healthy controls (HCs) were obtained from the Gene Expression Omnibus database. Twelve of twenty-six ferroptosis-related genes (FRG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In contrast to other bioinformatics studies examining the role of programmed death genes in RA ( Xie et al, 2023 ; Zhou et al, 2023 ), this study focused on the diagnostic value of autophagy-related genes in RA. In addition, compared to the previous study ( Fan et al, 2023 ), this research utilized three machine learning algorithms to screen diagnostic biomarkers for the construction of the diagnostic model that showed excellent diagnostic efficacy in multiple cohorts containing samples from different tissues and diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to other bioinformatics studies examining the role of programmed death genes in RA ( Xie et al, 2023 ; Zhou et al, 2023 ), this study focused on the diagnostic value of autophagy-related genes in RA. In addition, compared to the previous study ( Fan et al, 2023 ), this research utilized three machine learning algorithms to screen diagnostic biomarkers for the construction of the diagnostic model that showed excellent diagnostic efficacy in multiple cohorts containing samples from different tissues and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The production of IL-17 and IFN-γ from CD4 T cells in peripheral blood may directly contribute to the pathogenesis of RA (Park et al, 2014), while TNFSF10 may selectively activate CD4 T cells to promote IFN-γ production (Tsai et al, 2004), indicating that TNFSF10 may be a potential therapeutic target for RA. In contrast to other bioinformatics studies examining the role of programmed death genes in RA (Xie et al, 2023;Zhou et al, 2023), this study focused on the diagnostic value of autophagyrelated genes in RA. In addition, compared to the previous study (Fan et al, 2023), this research utilized three machine learning algorithms to screen diagnostic biomarkers for the construction of the diagnostic model that showed excellent diagnostic efficacy in multiple cohorts containing samples from different tissues and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A separate study demonstrated the presence of two ferroptosis clusters in the RA synovium that exhibit distinct immune profiles and ferroptosis sensitivity. [ 30 ] The development of appropriate clinical treatment plans for different groups of ferroptotic cells is beneficial for treating RA.…”
Section: Iron Metabolism and Arthritismentioning
confidence: 99%